The Rise of Post-truth Populism in Pluralist Liberal Democracies: Challenges for Health Policy - Ewen Speed; Russell Mannion (Kerman University of Medical Sciences, 2017)
Recent years have witnessed the rise of populism and populist leaders, movements and policies in many pluralist liberal democracies, with Brexit and the election of Trump the two most recent high profile examples of this backlash against established political elites and the institutions that support them. This new populism is underpinned by a post-truth politics which is using social media as a mouthpiece for 'fake news' and 'alternative facts' with the intention of inciting fear and hatred of 'the other' and thereby helping to justify discriminatory health policies for marginalised groups. In this article, we explore what is meant by populism and highlight some of the challenges for health and health policy posed by the new wave of post-truth populism.